KAJIAN PENGGUNAAN ANTIRETROVIRAL PASIEN HIV DI PUSKESMAS KOTA SEMARANG - Sulistiyanto, FX; Anggoro, A. Barry (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2024)
HIV is a human immunodeficiency virus that causes AIDS. ARV administration aims to reduce the number of viruses so that it will improve the immune status of HIV patients and reduce deaths due to opportunistic infections. This study aims to determine the characteristics of HIV patients who use antiretrovirals based on age, gender, and occupation as well as CD4 values ​​and to determine the description of antiretroviral use in HIV patients at the Semarang City Health Center in 2023. This research is a non-experimental study using retrospective data collection techniques. The research objects used were medical record data and laboratory values ​​(CD4) of HIV patients. Based on the research results, it is known that the majority of HIV patients are male with a percentage of 85%, while women make up 15%. Patients aged 26-35 years mostly suffer from HIV with a rate of 39%. Most patient jobs are in the private sector with a percentage of 92%. The CD4 value of most HIV patients is below 350 cells/mm³ with a rate of 37%, which shows that the HIV patient's immunodeficiency is in the moderate-severe category. Most antiretroviral therapy is given using KDT (Tenofovir + Lamivudine + Efaviren) with a percentage of 70%.